Unraveling the microbial contamination characteristics of pork farms and disinfection efficacy assessment via high-throughput sequencing - Feng Liu; Jiele Ma; Lichang Sui; Wen Wang; Yingping Xiao; Qingli Dong; Xingning Xiao (Animal Diseases)
Abstract The contamination of pork during breeding can negatively impact both food quality and safety. Sodium dichloroisocyanurate (NaDCC), a chlorine-containing disinfectant, is widely used in animal environments. In this study, 16S rRNA sequencing was used to determine the bacterial communities in a pork farm. We also assessed the effectiveness of NaDCC disinfection by analyzing microbial diversity. The results revealed that the predominant genera in pork skin samples and environmental samples were Staphylococcus and Acinetobacter, respectively. Escherichia coli and Streptococcus equinus were present in all the samples, suggesting that NaDCC is not fully effective in preventing zoonotic pathogen contamination. The Chao1 and Shannon indices for sow skins increased after disinfection. No significant differences were observed in the microbiological composition of sow barn samples before and after disinfection (p > 0.1). Additionally, bacterial abundance in sow skin was strongly correlated with abundance on pen floors (r = 0.906, p < 0.05), indicating potential cross-contamination between these sample types. Conversely, the bacterial abundance in the floor samples was weakly correlated with that in the other samples, suggesting that NaDCC is effective as a decontaminant. This study provides valuable insights into microbial contamination on pork farms and underscores the importance of proper disinfection practices. This study also offers scientific recommendations for improving disinfection protocols.